PERANAN LEMBAGA PEMBERDAYAAN MASYARAKAT DESA DALAM MENINGKATKAN PARTISIPASI MASYARAKAT TERHADAP PEMBANGUNAN DI DESA BINALANG - Hendry Rumengan (Jurnal Hukum dan Sosial Politik, 2023)
A role is a set of behaviors expected of a person according to his social position. Roles are based on rules and expectations because it is the role that explains what individuals must do in a given situation in order to meet their own expectations or the expectations of others. The purpose of this research is to know the role of Village Community Empowerment Institution in Binalang Village, and this research uses qualitative research method. Instrument researchers are researchers themselves. From the results of this study concluded that the role of LPMD in Binalang Village is not optimal, this is seen from the low ability of LPMD to increase community participation and lack of ability to plan development. To overcome the problems related to the low role of the Community Empowerment Institution, it is necessary to train the quality improvement program of human resources for LPMD management in the form of providing training with orientation to the main task and function of LPMD itself.